Case report: Non-linear evolution of oxytocin informs YBOCS changes post-DBS of the bed nucleus of the stria terminalis for treatment resistant OCD - Belge, Jean-Baptiste; Geenen, Vincent; Salado, Anne L.; Kaschten, Bruno; Martin, Didier; Scantamburlo, Gabrielle (Frontiers in Psychiatry, 2025)
IntroductionObsessive-compulsive disorder (OCD) is a challenging neuropsychiatric condition with a subset of patients remaining refractory to conventional treatments. Deep brain stimulation (DBS) of the bed nucleus of the stria terminalis (BNST) has shown promise for severe, treatment-resistant OCD. This case report examines the relationship between plasma oxytocin levels and OCD symptom severity following BNST-DBS.MethodsA 36-year-old patient with long-standing, treatment-resistant OCD underwent stereotactic implantation of DBS electrodes at the BNST. Postoperative assessments included OCD symptom severity using the Yale-Brown Obsessive Compulsive Scale (YBOCS) and plasma oxytocin levels, measured at 12 time points over three years. Longitudinal and correlational analyses were performed using linear and polynomial regression models.ResultsNon-linear trends in oxytocin levels were identified, with polynomial regression revealing a significant quadratic term, suggesting a parabolic trend. Strong positive correlations were found between changes in oxytocin levels and YBOCS total, obsession, and compulsion scores.ConclusionThe findings suggest a significant non-linear evolution of oxytocin levels and a positive correlation with OCD symptom changes following BNST-DBS. Oxytocin levels could serve as a biomarker for DBS efficacy if this finding is replicated in larger studies.